2006
DOI: 10.1007/s00018-005-5548-7
|View full text |Cite
|
Sign up to set email alerts
|

The translocation motif of hepatitis B virus improves protein vaccination

Abstract: Cell-penetrating peptides (CPPs) have been shown to improve antigen loading of dendritic cell vaccines. Here we asked whether fusion of a CPP to a protein improves its immunogenicity when this fusion protein is directly applied as vaccine. We used the cell-penetrating translocation motif (TLM) derived from the hepatitis B virus, because no size limitation of cargos has been observed. Increased immunogenicity was observed when TLM was fused to ovalbumin (TLM-ova). TLM-ova was found to be superior to ova in indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…or s.c.) to maximize the probability of targeting DCs. This route of administration of CPP-based cancer vaccines has been proven to be efficacious, as revealed by strong Ag-specific T-cell responses elicited against various Ag [21, 24, 47, 72]. An elegant study of Zhang et al clearly showed that s.c. administration of a CPP-based vaccine efficiently triggers peripheral DCs [27].…”
Section: Route Of Administration Of Cpp-based Cancer Vaccinesmentioning
confidence: 99%
“…or s.c.) to maximize the probability of targeting DCs. This route of administration of CPP-based cancer vaccines has been proven to be efficacious, as revealed by strong Ag-specific T-cell responses elicited against various Ag [21, 24, 47, 72]. An elegant study of Zhang et al clearly showed that s.c. administration of a CPP-based vaccine efficiently triggers peripheral DCs [27].…”
Section: Route Of Administration Of Cpp-based Cancer Vaccinesmentioning
confidence: 99%
“…The fourth class of CPPs are peptides derived from hydrophobic sequences of proteins which naturally interact with plasma membrane, e.g. integrin b3-fragment [16], Hepatitis B virus translocation motif [17] or calcitonin fragment (Table 1) [18].…”
Section: Cpp Classificationmentioning
confidence: 99%
“…Thus, we next evaluated the amplitude and nature of the humoral and cell-mediated immunity developed in vivo in response to both prophylactic and therapeutic vaccines in nicotine-exposed mice. We implemented the OVA-EG7 immunogenic tumor model (31) used by others in preclinical studies testing vaccine formulation for cancer and infections (32)(33)(34)(35)(36)(37)(38)(39). To study the effects of nicotine on prophylactic vaccination, WT C57BL/6 mice were implanted with osmotic pumps containing nicotine and then were vaccinated twice s.c. at the base of the tail with OVA protein mixed with the Th1 adjuvants LPS or CpG.…”
Section: Nicotine Exposure Compromises the Effectiveness Of Both Propmentioning
confidence: 99%